An Evaluation of English-to-Yoruba Translations of some Concepts by Selected Radio News Bulletins - Samson Adeyeye Dare; Francis Yede (Yoruba Studies Review, 2021)
This study examines translations of selected official names/titles contained in news broadcasts in the Yorùbá-speaking part of Nigeria, interrogating their adequacy and appropriateness. Sixty-five concepts/titles extracted from one hundred news bulletins presented by five radio stations across the Yorùbá-speaking states of Nigeria are examined. The study is prompted by an intuitive feeling of inaccuracy and inappropriateness of important words in news broadcasts in Yorùbá and predicated upon the fact that misinformation can be as pernicious as lack of information. The renderings of the concepts in Yorùbá are compared with their original versions in English, revealing translation weaknesses such as semantic narrowing, expansion, wordiness, and sometimes even unwitting distortions. It concludes by emphasizing the adoption of appropriate translation strategies and a more rigorous engagement with the texts as a way of guarding against unintended distortions and misinformation.